2015
DOI: 10.1016/j.jinf.2015.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Administration of antibiotic agents before intraoperative sampling in orthopedic infections alters culture results

Abstract: Summary Summary: Many physicians and surgeons think that prescribing antibiotics before intraoperative sampling does not alter the microbiological results. Methods: Case-control study of adult patients hospitalized with orthopedic infections. Results: Among 2740 episodes of orthopedic infections, 1167 (43%) had received antibiotic therapy before surgical sampling. Among these, 220 (19%) grew no pathogens while the proportion of culture-negative results in the 2573 who had no preoperative antibiotic therapy was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
51
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(56 citation statements)
references
References 28 publications
1
51
0
2
Order By: Relevance
“…Also, since we included all hospitalized patients, this study reflects real‐life conditions at our centre's clinical practice, thus reducing selection bias. Our rate of clinical recurrence (17%) is similar to that reported in the literature (15%, 18% and 19% depending on the studies). This is equally true regarding our microbiology‐confirmed recurrence rate of 8%, which is shared by other groups (6%‐8%, 9%, and 8%) as well.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Also, since we included all hospitalized patients, this study reflects real‐life conditions at our centre's clinical practice, thus reducing selection bias. Our rate of clinical recurrence (17%) is similar to that reported in the literature (15%, 18% and 19% depending on the studies). This is equally true regarding our microbiology‐confirmed recurrence rate of 8%, which is shared by other groups (6%‐8%, 9%, and 8%) as well.…”
Section: Discussionsupporting
confidence: 90%
“…Prior to admission or initial surgical procedure, 96 episodes (20%) already received systemic antibiotic therapy, but exact data on duration or dosage are lacking. Following amputation, median duration of systemic antibiotic administration was 7 days (IQR, 1‐16 days) and median duration of parenteral use was 5 days (IQR, 0‐12 days).…”
Section: Resultsmentioning
confidence: 99%
“…If the waiting time for surgery is significant, patients may receive preemptive antibiotic therapy. This practice can alter the microbiological results of intraoperatively obtained samples [18]. Although we did not find a statistical difference in bacterial growth between patients with and without antimicrobial prophylaxis, we cannot estimate the role of antimicrobial agents in susceptible microorganisms only.…”
Section: Discussionmentioning
confidence: 68%
“…Zhorne et al [7] reported that longer durations of preoperative antibiotics were associated with more culture-negative results in cases of pediatric hematogenous osteomyelitis. Similarly, in a retrospective cohort of patients with mixed orthopedic infections, Al-Mayahi et al [6] found that 19% of patients who received preoperative antibiotics had culture-negative results, whereas only 6% of those who did not receive preoperative antibiotics had culture-negative results. In contrast, Ghanem et al [11] found no statistical difference in the proportion of negative tissue cultures between patients with total knee arthroplasty infection who were exposed and not exposed to perioperative antibiotics.…”
Section: Discussionmentioning
confidence: 98%
“…Previous authors have shown that a single perioperative antibiotic administered before operations for suspected prosthetic joint infection is not associated with a larger proportion of negative cultures [3, 4]. The effect of multiple days of antibiotics on operative cultures has been studied in revision hip arthroplasty [5], mixed orthopedic infections [6], pediatric osteomyelitis [7], and pyogenic vertebral osteomyelitis [8, 9] with conflicting results. The effect of preoperative antibiotics on DFI cultures has not been studied.…”
mentioning
confidence: 99%